2003
DOI: 10.1021/ic020569w
|View full text |Cite
|
Sign up to set email alerts
|

Novel Iron(III) Complexes of Tripodal and Linear Tetradentate Bis(phenolate) Ligands:  Close Relevance to Intradiol-Cleaving Catechol Dioxygenases

Abstract: Four new iron(III) complexes of the bis(phenolate) ligands N,N-dimethyl-N',N'-bis(2-hydroxy-3,5-dimethylbenzyl)ethylenediamine [H2(L1)], N,N-dimethyl-N',N'-bis(2-hydroxy-4-nitrobenzyl)ethylenediamine [H2(L2)], N,N'-dimethyl-N,N'-bis(2-hydroxy-3,5-dimethylbenzyl)ethylenediamine [H2(L3)], and N,N'-dimethyl-N,N'-bis(2-hydroxy-4-nitrobenzyl)ethylenediamine [H2(L4)] have been isolated and studied as structural and functional models for the intradiol-cleaving catechol 1,2-dioxygenases (CTD). The complexes [Fe(L1)Cl]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
178
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(193 citation statements)
references
References 92 publications
(97 reference statements)
15
178
0
Order By: Relevance
“…[44] Also several works were published on functional mimics of both intradiol and extradiol-cleaving enzymes. [45][46][47] These structure-function studies highlight the great plasticity of the enzyme active site and make these enzymes particularly promising for protein-engineering studies that aim both at a more precise characterisation of the catalytic properties and at reshaping for technological applicative purposes. To date, to our knowledge, no protein-engineering approach has been performed on catechol 1,2-dioxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…[44] Also several works were published on functional mimics of both intradiol and extradiol-cleaving enzymes. [45][46][47] These structure-function studies highlight the great plasticity of the enzyme active site and make these enzymes particularly promising for protein-engineering studies that aim both at a more precise characterisation of the catalytic properties and at reshaping for technological applicative purposes. To date, to our knowledge, no protein-engineering approach has been performed on catechol 1,2-dioxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…The most threatening consequence of such iron behavior is the possibility of generating radicals: for example, · OH [generated directly by Fe II species: Equation (6)] has a lifetime of 10 -9 s; therefore its tremendous activity is directly associated with the potential for serious deleterious effects. The assumption of the high redox activity of Fe 3+ complexes leading to the formation of radicals was based (as supposed) on the following well-established hypotheses: (1) Haber-Weiss process [see Equations (5) and (6)] found for iron ions [38] and also shown for the [Fe(EDTA)] -complex in vitro, [39,40] (2) direct coordination of water molecules even in polydentate but rigid Fe 3+ chelates (e.g., the above-mentioned EDTA, and also other N,O-chelates), [41] and (3) efficient redox activity of many iron enzymes leading to the transformation of radicals, including potentially dangerous reactive oxygen species (ROS). [42] However, these issues have been elaborated and several studies have shown that the direct coordination of oxygen does not necessarily have to lead to serious deleterious effects.…”
Section: Iron(iii) Contrast Agentsmentioning
confidence: 98%
“…In the complexes 3 and 10 this absorption is obscured by very intense π-π* charge-transfer transitions, due to the phenyl rings of the dbm ligand for 3 and the nitro groups on the dnpppy ligand for 10. [7,39] All manganese complexes show an absorption at around 230-260 nm, which is attributed to a π-π* transition originating from the (substituted) pppy ligand.…”
Section: Electronic Absorption Spectroscopymentioning
confidence: 99%